(3GdLGeY aj GdCOhjI GdeaQOIs - (3YHO Gddg Hf CMeO GdeGdbj, VjGA GdOjf, GHf GdHjWGQ , J (B646 (3g` s
(3ChdgG (B:s
(3hHYO , aEfg deG HGdChGeQ GdeWGYI GdehdhjI GdYGdjI GdSdWGfjI GdedcjI GdZQV GdChd GSJjYGH Gdbhd ai GdCOhjI GdeaQOI s
(3BNQgG (B:s
(3CNQg ZjQ hGVM gh GdRjJ GdefJL ef GdRjJhf GdaL hjSejI Cgd GdYQGb dCfg jCJi ef GdTGe s
(3bWYI ef fSNI NGeSI eRhbI GdWGdYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG RNGQa s
Keywords: (3GdWHs